Assessing the climatic suitability of Bambara groundnut as an underutilised crop to future climate projections in Sikasso and Ségou, Mali - Ezekannagha, Ezinwanne (Department of Environmental and Geographical Science, 2021)
This study evaluates how future climatic projections will affect the suitability of bambara groundnut (Vigna subterranean(L) Verdc.), a type of underutilised crop in Sikasso and Ségou, southern Mali. This study was performed using a simulation approach, which considered the potential changes in suitability due to projected changes in two climate variables; temperature and precipitation. Monthly outputs of the two climate variables from 10 CORDEX bias-corrected regional projections under the Representative Concentration Pathway (RCP) 8.5 were applied. The suitability index range of bambara groundnut was projected, using the Ecocrop suitability model, considering three time periods: historical (1975-2005), near-term (2011-2040), and end of century (2070-2099). The results of this study showed that the model captured a long planting window for the crop in the regions across the time periods. With the projected increase in future climatic conditions, the suitability index range of bambara groundnut is projected to increase across the months suitable for planting the crop. Furthermore, Sikasso is projected to maintain a high suitability index in the near-term, and by the end of century, Ségou is expected to experience a potential increase in suitability index range and suitable areas, especially by the end of century. The results indicate that the CORDEX projections and suitability modelling technique applied in the study captured well the suitability of bambara groundnut in the regions which can help the farmers in making planting decisions. These results suggest an opportunity for optimal utilisation of the crop in the regions, as with a long planting window and expansion in suitable areas, farmers in the regions can plant multiple times and have more suitable areas to cultivate. This study contributes to improving the decision-making surrounding the promotion of underutilised crops as part of the strategy for climate-resilient agriculture and food security in Sikasso and Ségou.